The direct and indirect impact of pharmaceutical industry in economic expansion and job creation: Evidence from bootstrapping and normal theory methods - Rizwan Raheem Ahmed; Jolita Vveinhardt; Dalia Štreimikienė (Amfiteatru Economic Journal, 2018)
The objective of this research article is to examine the role of Pakistan's pharmaceutical industry in job creation opportunities, with the sacred intention to eradicate poverty, and expansion in economic activities. This research is quantitative in nature, and the data is directly gathered through closed-ended questionnaires from 300 respondents. Besides predictors', four mediating variables have also been taken into consideration that contribute indirectly in job creation opportunities. Bootstrapping and Normal theory methods have been employed in order to examine the impact of predictors' and mediating variables. The result of this research confirmed that pharmaceutical industry plays a vital role in job creation in Pakistan. It is further concluded that the pharmaceutical industry has a direct and significant impact in job creation by providing indigenous and direct job opportunities in sales, marketing, and other supporting departments for both skilled and unskilled workers. Pharmaceutical industry also provides indirect job opportunities through other industries, which are very much linked with this industry, such as: pharmaceutical distributors, dealers, retailers, wholesalers, hotel industry, and event management industry. It is also determined that pharmaceutical industry is acting like knowledge and skills imparting institutions. Therefore, skilled-based training and organizational learning are major mediating variables that transform unskilled people into human assets, which further trigger the future job prospects. Since pharmaceutical industry is one of the biggest industries in Pakistan, providing plenteous opportunities of new jobs with consistent growth. Thus, mediating variables such as motivation and interpersonal influence also preceded an active role in new job creation.
Keywords: B23; C12; I3; J2; L6; 330; job creation; pharmaceutical industry; bootstrapping method; normal theory method